Encouraging Youth Engagement in Marine Protected Areas: A Survey of Best Practices in Canada - Garmulewicz, A (John Wiley and Sons Ltd, 2019)
A holistic approach to stakeholder participation is emerging where youth are increasingly being recognized as core stakeholders in community-based conservation efforts. A growing number of youth-focused marine conservation initiatives and representation at international marine conservation conventions demonstrate that youth are taking an active role in marine conservation worldwide. This paper surveys current best practices in youth engagement in marine protected areas (MPAs) in Canada, across 10 different engagement strategies. These are: facilitate learning through experiential education; include studies of MPAs in academic and community programmes; utilize multimedia opportunities, including social media, film, website, and apps; provide meaningful volunteer opportunities; deliver professional development sessions for youth initiative building; create youth councils to assist organizations in an advisory role; hire youth for employment in internships, co-ops and junior positions within organizations; showcase young people as Youth Ambassadors of MPAs; share opportunities through effective outreach and promotion; and, integrate under-represented perspectives in MPAs. Recommendations are drawn from the case studies within each engagement strategy. Collectively, they offer insight into the variety of ways the international community can support, highlight and advance youth participation in MPAs. © 2019 John Wiley & Sons, Ltd.
Keywords: best practices; engagement; marine conservation; marine protected areas; youth